2004
DOI: 10.4049/jimmunol.172.8.4907
|View full text |Cite
|
Sign up to set email alerts
|

Selective Impairments in Dendritic Cell-Associated Function Distinguish Hepatitis C Virus and HIV Infection

Abstract: Impaired APC functions may play important roles in chronicity of hepatitis C virus (HCV) and HIV infections. To investigate the separate and combined effects of HCV and HIV infection on immature dendritic cells (DCs), we evaluated myeloid-derived DC (MDC) and plasmacytoid-derived DC (PDC) frequencies and functions, measured by Toll-like receptor ligand-induced IFN-α and IL-12, in healthy controls and subjects with chronic HCV, HIV, and HCV-HIV infection. To evaluate the relation between innate and adaptive imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
137
5
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 60 publications
(88 reference statements)
17
137
5
6
Order By: Relevance
“…Freshly collected PBMC were stimulated with one of the following TLR ligands: TLR3L poly (I:C) or TLR9L CpG oligodeoxynucleotides (23,(32)(33)(34). Poly(I:C) stimulates mDCs to secrete IL-12 (23,33), whereas CpG stimulates pDCs to secrete IFN-␣ secretion (23,34).…”
Section: Restoration Of Circulating Impaired Mdcs and Pdcs Correlatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Freshly collected PBMC were stimulated with one of the following TLR ligands: TLR3L poly (I:C) or TLR9L CpG oligodeoxynucleotides (23,(32)(33)(34). Poly(I:C) stimulates mDCs to secrete IL-12 (23,33), whereas CpG stimulates pDCs to secrete IFN-␣ secretion (23,34).…”
Section: Restoration Of Circulating Impaired Mdcs and Pdcs Correlatedmentioning
confidence: 99%
“…Freshly prepared PBMC populations (2 ϫ 10 6 cells/0.5 ml/well) were stimulated in 24-well plates with medium alone, 50 g/ml poly(I:C) (Amersham), or 6 g/ml CpG 2216 (Sangon) for 24 h at 37°C in the presence of penicillin, streptomycin, L-glutamine, and 10% FCS (23). Cell-free supernatants were harvested and tested in duplicate for IFN-␣ or IL-12 by use of a commercial ELISA kit according to the manufacturer's instructions (BioSource International).…”
Section: Cytokine Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14 In cHC, an impairment of monocyte-derived dendritic cells has been suggested in several studies [15][16][17][18] and could be due to direct infection of these cells by HCV. 19 Along these lines, infection of pDCs, 20 a reduced relative frequency of pDCs, and a reduced capacity to produce IFN-␣ have recently been shown in cHC [21][22][23] and during IFN-␣ treatment, 24 but their relevance-particularly during the acute phase of HCV infection, when the decision of viral clearance versus persistence is made-has not been studied.…”
mentioning
confidence: 99%
“…Similarly, while some studies suggested that the functionality of DCs was impaired during chronic infection, e.g. mDCs being poor activators of CD4 + T cells (AuffermannGretzinger et al, 2001;Bain et al, 2001;Dolganiuc et al, 2008;Kanto et al, 1999) and pDCs producing less IFN-a (Anthony et al, 2004;Yonkers et al, 2007), other studies reported that mDCs and pDCs from chronically infected patients remained functional (Decalf et al, 2007;Lai et al, 2007;Longman et al, 2004). It is interesting to note that, however, several groups have reported that the frequency of circulating mDCs and pDCs during chronic HCV infection is reduced, probably due to an intrahepatic enrichment (Dolganiuc et al, 2006;Lai et al, 2007;Mengshol et al, 2009;Nattermann et al, 2006;Wertheimer et al, 2004).…”
Section: Role Of Dcs In Hcv-infected Humansmentioning
confidence: 99%